(untitled) (Web of Teachers: Inderscience Research, 2025)
This article presents an artistic analysis of the three main regional schools of traditional Uzbek singing: Fergana-Tashkent, Bukhara, and Khiva styles. The aesthetic characteristics, performance techniques, melodies, instruments, and poetic materials of each school are described. The article also reveals the musical and cultural uniqueness of each regional school through the work of famous singers. Additionally, it provides insights into the interrelation between these schools and their roles in the development of national art.